Comparative assessment of genetic diversity in Indian and exotic neem (Azadirachta indica) using AFLP markers - SINGH, RAKESH; RANDHAWA, G J (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted to assess genetic divergence among the 14 neem (Azadirachta indica A. Juss) lines collected from Punjab, Haryana, Rajasthan, India and 8 exotic lines procured from Arid Forest Research Institute, Jodhpur, using amplified fragment length polymorphism (AFLP) marker. Fourteen selective AFLP primer combinations were used which generated a total of 758 amplicons with an average of 54.14/primer. All the 14 primers used in the study also generated 116 accessions specific bands. Genetic relationship within the lines was evaluated by generating a similarity matrix based on Jaccard’s similarity co-efficient. The phenetic dendrogram generated by UPGMA demonstrated that neem lines collected constitutes a broad genetic base with the similarity values ranging from 0.21 to 0.89. The cluster analysis showed that exotic and indigenous lines are grouping in separate clusters, depicting that exotic and indigenous gene pool is different. Principal component analysis showed that the first 3 components showed 74% of variation with indigenous gene pool more diverse in comparison to exotic gene pool.